2020
DOI: 10.1371/journal.pone.0221543
|View full text |Cite
|
Sign up to set email alerts
|

Insights on aquatic microbiome of the Indian Sundarbans mangrove areas

Abstract: Background Anthropogenic perturbations have strong impact on water quality and ecological health of mangrove areas of Indian Sundarbans. Diversity in microbial community composition is important causes for maintaining the health of the mangrove ecosystem. However, microbial communities of estuarine water in Indian Sundarbans mangrove areas and environmental determinants that contribute to those communities were seldom studied. Methods Nevertheless, this study attempted first to report bacterial and archaeal co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 69 publications
(90 reference statements)
2
20
0
Order By: Relevance
“…The archaeal community was dominated by members of the Thermoplasmata, Thaumarchaeota, and Methanococcales ( Figure 4 , Figure S1 ). This was in accordance with other studies that have identified Rhodobacteraceae, SAR86 clade, Actinobacteria, and Flavobacteriaceae, and Thaumarchaeota as the most abundant taxonomic groups ( Dhal et al., 2020 ). Rhodobacteraceae has been found to be dominant in mangrove-dominated estuaries, and members of this family are associated with marine phytoplankton blooms where they play a role in transformations of derived phytoplankton organic matter ( Ghosh et al., 2010 ; Simon et al., 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…The archaeal community was dominated by members of the Thermoplasmata, Thaumarchaeota, and Methanococcales ( Figure 4 , Figure S1 ). This was in accordance with other studies that have identified Rhodobacteraceae, SAR86 clade, Actinobacteria, and Flavobacteriaceae, and Thaumarchaeota as the most abundant taxonomic groups ( Dhal et al., 2020 ). Rhodobacteraceae has been found to be dominant in mangrove-dominated estuaries, and members of this family are associated with marine phytoplankton blooms where they play a role in transformations of derived phytoplankton organic matter ( Ghosh et al., 2010 ; Simon et al., 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…Large amounts of particulate and dissolved organic matter are characteristic of the watercourses flowing into the Bay of Bengal. Gammaproteobacteria and Alphaproteobacteria dominated the bacterial community composition of the waters of the Bay of Bengal (Ghosh and Bhadury, 2018;Rajpathak et al, 2018;Fernandes et al, 2019;Dhal et al, 2020) and these classes together with Deltaproteobacteria were detected abundantly in sediments of the Sundarbans (Basak et al, 2015). In this study, Deltaproteobacteria were mainly represented by Geobacter at K8 with relevance for the arsenic cycle (Gnanaprakasam et al, 2017).…”
Section: Bacterial Community Composition and Potential Roles Across Tmentioning
confidence: 49%
“…Another fascinating observation of the current study was the exceptionally high richness of Woesearchaeota (58.9% of all OTUs, 12.8% of sequences). High proportions of Woesearchaeota had been recovered from mangrove sediments worldwide, e.g., in China ( 22 , 36 , 44 ) and India ( 45 ). This might be attributable to their anaerobic heterotrophic lifestyle and diverse metabolic capabilities, such as the utilization of starch or sugar, acetate fermentation, and metabolism of hydrogen and nitrogen ( 33 , 46 ), which made them flourish in mangrove sediments, a habitat with nutrient-rich and anaerobic conditions.…”
Section: Discussionmentioning
confidence: 99%